Report from the Visegrad Fund Workshop in Bratislava - Kováčová, Viktória (Lidé města, 2023)
On the 23rd and 24th of March 2023, the Faculty of Social and Economic Sciences of Comenius University (FSEV UK) in Bratislava hosted an interesting and enriching hybrid workshop. It was organized on the occasion of a Visegrad Fund project entitled “Assessing the study of religious change in Central-Eastern Europe: New fields in the study of religious change in Central-Eastern Europe”. During the two days, junior and senior researchers discussed issues related to religion and spirituality, as well as religious changes and processes in V4 countries. The primary goals of the project were to “strengthen cooperation between scholars in the field of religion in the V4 [countries], to make current research in this field of study visible, and to support social dialogue on religious changes in [the given] regions” (FSV UK 2023). The primary goal of the organizers of the workshop was to create a safe environment where young researchers could receive constructive feedback and potential suggestions for improvement, which could then strengthen their experience and interest in their given field of study.